HUBUNGAN KEPEMIMPINAN DENGAN KINERJA KESEHATAN DI RUMAH SAKIT UMUM MEDAN TERE MARGARETH - Marlen Sitepu; Novrika Silalahi; Vitrilina Hutabarat (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
Based on data from the Hospital Accreditation Commission, out of 2,379 private and state hospitals in Indonesia, only 1,032 hospitals (43.4%) are accredited. This can reflect the performance of health workers in hospitals is not optimal, because the performance of health workers is one of the determinants of organizational success in achieving hospital goals. The purpose of this study is to link leadership with the performance of health workers. This type of research is analytic with cross-sectional design. The study was conducted at the Tere Margareth General Hospital in Medan. The study population was 62 people, and all were sampled. Data analysis used univariate analysis, bivariate analysis with chi-square test at a confidence level of 95% ( = 0.05). The results of the study found that 24.2% of respondents stated that leadership was lacking, and also found the performance of health workers 32.3% in the less category. There is a significant relationship between leadership and the performance of health workers at Tere Margareth General Hospital Medan, p = 0.012 <0.05. It was suggested that the Management of the Tere Margareth General Hospital in Medan to improve the leadership style that was lacking so that it could be an example or role model for health workers so that in the end the performance of each individual would increase.